Global status of antimicrobial resistance in clinical Enterococcus faecalis isolates: systematic review and meta-analysis - Lingbo Guan; Masoumeh Beig; Lina Wang; Tahereh Navidifar; Samaneh Moradi; Faezeh Motallebi Tabaei; Zahra Teymouri; Mahya Abedi Moghadam; Mansour Sedighi (BMC, 2024)
Abstract Background Due to the increasing emergence of antibiotic resistance in Enterococcus faecalis (E. faecalis), it indicated as potentially opportunistic pathogen causing various healthcare-associated and life-threatening diseases around the world. Objective The aim of this meta-analysis was to evaluate the weighted pooled resistance rates in clinical E. faecalis isolates based on over time, areas, antimicrobial susceptibility testing (AST), and infection source. Methods We searched the studies in PubMed, Scopus, and Web of Science (November 30, 2022). All statistical analyses were carried out using the statistical package R. Results The analysis encompassed a total of 74 studies conducted in 28 countries. According to the meta-regression, the chloramphenicol, fosfomycin, imipenem, linezolid, minocycline, norfloxacin, quinupristin-dalfopristin, and tetracycline resistance rate increased over time. Analysis revealed statistically significant differences in antibiotic resistance rates for ampicillin, chloramphenicol, erythromycin, gentamicin, penicillin, rifampicin, teicoplanin, tetracycline, and vancomycin across various countries. Conclusions Globally, the prevalence of drug resistant E. faecalis strains are on the increase over time. Daptomycin and tigecycline can be an effective agent for the treatment of clinical E. faecalis infections. Considering the low prevalence of antibiotic resistance in continents of Europe and Australia, it is suggested to take advantage of their preventive strategies in order to obtain efficient results in other places with high prevalence of resistance.